Individual investors’ personality traits and overconfidence biases - Tharshiga, P.; Yogendrarajah, R. (Sri Sairam Institute of management studies., 2020)
The term finance has been used from several years, while behavioural finance is quite new field in modern financial studies which takes under thought psychology of human being. Theories comes under behaviour finance are based on the psychology, which tries to develop understanding how behaviour of individual investors is being influenced by their emotions and cognitive biases. The present study examines how personality traits are influencing on investors’ over confidence bias. For the study purpose 330 samples are drawn from Colombo stock exchange investors. Analysed results show that there is negative relationship between individual personality traits (extroversion, consciousness, neuroticism, openness) and overconfidence bias. Agreeableness personality has negative relationship with overconfidence bias but the relationship is not statistically significant. This study suggested to the investors who should be aware of psychological biases with which they can face by knowing their own personality traits and also make decisions depending on their financial risk. Further researchers recommend educated individuals evaluate the investment's programs consciously and consult with others about their own ideas.
Keywords: Investors’ personality; Behavioural Finance; Overconfidence